THE EFFECT OF LOAN TO DEPOSIT RATIO (LDR), INFLATION, INTELLECTUAL CAPITAL AND NET PROFIT MARGIN (NPM) ON PROFITABILITY IN CONVENTIONAL BANKS LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2014-2018 PERIOD - Wenny Anggita (Riset Akuntansi Keuangan, 2021)
This study aims to analyze the effect of Loan to Deposit Ratio, Inflation,Intellectual Capital and Net Profit Margin on profitability. This research usesthis type of research with a quantitative approach by using panel data andprocessed using e-Views software. The sample used was 29 ConventionalBanks listed on the Indonesia Stock Exchange 2014-2018. The results of thisstudy reveal that the Loan to Deposit Ratio, Inflation and Net Profit Marginhave a positive effect on profitability. While Intellectual Capital does not havea positive effect on profitability.